The Demand for Chinese + Talent Training: A Case Study of Chinese Language Program at Universitas Sebelas Maret - Phanata, Stephanie (Published by Confucius Institute UNS, 2024)
The Belt and Road Initiative has brought chances for International Chinese Language Education in the new era and has had a positive impact on the progress of Chinese language education in countries along the route, increasing the demand for “Chinese +” talent training in various fields, such as industry, trade and economy. Due to the different economic and industrial structures and development levels of various countries, the status and degree of dissemination of Chinese also vary, and the demand for “Chinese +” talents in various countries has national characteristics. Therefore, in addition to fully considering the teaching needs and market demand factors, we must also broaden the needs of Indonesian students and cultivate diversified “Chinese +” talents. From the angle of Indonesian students, what are the needs for “Chinese +” talent training in order to address the lack of translation skills in the industrial, trade and business sectors? The article uses questionnaires and interviews to investigate the personal information of Indonesian students, market demand in Indonesia, Chinese teaching conditions, and professional Chinese proficiency requirements, and proposes a talent training model for Indonesian students, aiming to provide a reference for promoting International Chinese Language Education in the Belt and Road Initiative.